2011
DOI: 10.1007/s00299-011-1162-3
|View full text |Cite
|
Sign up to set email alerts
|

A putative functional MYB transcription factor induced by low temperature regulates anthocyanin biosynthesis in purple kale (Brassica Oleracea var. acephala f. tricolor)

Abstract: The purple kale (Brassica Oleracea var. acephala f. tricolor) is a mutation in kales, giving the mutant phenotype of brilliant purple color in the interior. Total anthocyanin analysis showed that the amount of anthocyanins in the purple kale was up to 1.73 mg g(-1) while no anthocyanin was detected in the white kale. To elucidate the molecular mechanism of the anthocyanin biosynthesis in the purple kale, we analyzed the expression of structural genes and some transcription factors associated with anthocyanin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 28 publications
5
105
0
Order By: Relevance
“…While MYB6 is less characterized, MYB113 is in a small clade known to act in complexes with basic helix-loop-helix (bHLH) proteins to activate genes encoding enzymes acting in late stages of flavonol biosynthesis. MYB variants cause pigmentation variation in potato, tomato, and pepper [48], as well as in kale [49]. Pigmentation in apple skin and flesh is also regulated by MYB transcription factors [50].…”
Section: Resultsmentioning
confidence: 99%
“…While MYB6 is less characterized, MYB113 is in a small clade known to act in complexes with basic helix-loop-helix (bHLH) proteins to activate genes encoding enzymes acting in late stages of flavonol biosynthesis. MYB variants cause pigmentation variation in potato, tomato, and pepper [48], as well as in kale [49]. Pigmentation in apple skin and flesh is also regulated by MYB transcription factors [50].…”
Section: Resultsmentioning
confidence: 99%
“…Because it is an important factor that influences anthocyanin biosynthesis, the effect of cold stress has been extensively studied for various plants (Crifò et al 2011;Zhang et al 2011Zhang et al , 2012. Numerous previous reports have demonstrated that cold stress can efficiently promote the accumulation of anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
“…Jeannette et al (2000) found that heat girdling at the base of maize (Zea mays) leaves caused an increase in foliar sucrose concentrations compared with controls and that the anthocyanin content of girdled leaves then increased considerably within 36 h. The mechanistic connection between sugar and anthocyanin concentrations has been bolstered by findings that sugars induce gene transcription required for anthocyanin biosynthesis via the shikimic acid pathway (Hara et al 2003). Indeed, the expression of a range of anthocyanin biosynthetic genes (e.g., CHS, CHI, C4H, F3H, DFR, ANS, and UFGT) are enhanced by lowtemperature exposure (Zhang et al 2011;Zhang et al 2012), with sugar signaling initiating the biochemical cascades that trigger this (e.g., Vitrac et al 2000;Hara et al 2003). In addition to their influence on anthocyanin biosynthesis, increases in sugar concentrations may play a significant role in triggering leaf senescence, especially the loss of chlorophyll in leaves (Wingler et al 1998).…”
Section: Discussionmentioning
confidence: 95%